A Multimodal Discourse Analysis of Indonesian Beauty Product Advertisement Featuring Korean Celebrity on Instagram Post - Khoirunnisaa, Syifaa; Septiana Harti, Laily Maulida (Language Horizon: Journal of Language Studies, 2023)
This qualitative study investigated the visual and verbal elements of Indonesian beauty advertisements featuring Korean celebrities constructing representational meaning to engage consumers. Five Indonesian beauty products advertisements: Whitelab, Y.O.U, MS GLOW, Somethinc, and Azarine, were retrieved from Instagram and analysed using Generic Structure Potential by Cheong (2004), Transitivity System by Halliday & Matthiessen (2013), and Visual Grammar by Kress and Van Leeuwen (2006). The findings revealed that the visual component consists of Lead which is the most prevalent and instantly captures the reader's attention. Then, the Display shown is congruent. The visual element contains two representations of action process and circumstances of means. In the verbal component, the announcement is the most frequent element. Enhancers appear in the Instagram advertisement caption, verbal logos show emblems, tags capture product-related information, and Call-and-Visit is only present in Azarine advertisements. The Processes that occur in the verbal components are Mental, Existential, Relational, and Material Processes. However, The Material Process is most found in the Instagram caption instead of the poster's design. It enhances the sophistication and simplicity of the ad. Accordingly, verbal and visual modalities collaborate to portray aesthetic, bright, and charming essential to the brand's engagement.